Serum antioxidant status and mortality from influenza and pneumonia in US adults. Issue 12 (10th December 2022) - Kang, Habyeong; Hu, Howard; Park, Sung Kyun
Abstract: Objective: We examined the association between serum antioxidant status and mortality from influenza and pneumonia in US adults. Design: Serum concentrations of antioxidants included vitamin C, vitamin A, vitamin E, sum of α - and β -carotene, β -cryptoxanthin, lutein + zeaxanthin and lycopene. We computed total antioxidant capacity (TAC) as a measure of composite antioxidant status in serum. Survey-weighted Cox proportional hazard models were used to compute hazard ratios (HR) and 95 % CI comparing quartiles of each antioxidant and TAC. Setting: Data from the US National Health and Nutrition Examination Survey (NHANES)-III. Participants: A total of 7428 NHANES-III participants ≥45 years of age. Results: With a weighted-median follow-up of 16·8 years, 154 participants died from influenza/pneumonia. After adjustment for covariates, serum vitamin C, the sum of α - and β -carotene and TAC were nonlinearly associated with influenza/pneumonia mortality, with the statistically significant smallest HR at the third quartile v . the first quartile (HR = 0·38 (95 % CI: 0·19, 0·77), 0·29 (0·16, 0·51) and 0·30 (0·15, 0·59), respectively). HR comparing the fourth v . the first quartiles were weaker and nonsignificant: 0·57 (95 % CI: 0·27, 1·17), 0·70 (0·41, 1·19) and 0·65 (0·31, 1·35), respectively. Serum lycopene had a monotonic association with influenza/pneumonia mortality (HR = 0·43 (95 % CI: 0·23, 0·83) comparing the fourth v . the first quartile, P for trend = 0·01). Conclusions: The current study suggests that antioxidant intake as reflected by serum concentrations may reduce mortality risk from influenza or pneumonia in the US general population. These findings warrant further confirmation in other populations with different settings (e.g. a shorter-term association with influenza infection).